Loss to Follow-up and Developmental Delay in the Neonatal High-Risk Infant Follow-up Clinic - Christner, Lilia P.; Dabaja, Emman; Attar, Mohammad (American Journal of Perinatology, 2025)
Neonatal follow-up (NFU) clinics provide developmental assessments for infants at high risk for developmental delays. Disparities in NFU attendance and loss to follow-up (LTF) are well documented, but it is not known whether patients who are LTF have different developmental outcomes. The population of patients LTF from the NFU clinic is assumed to be homogenous, but we hypothesize there is a subpopulation of patients LTF who are receiving developmental care elsewhere. Our objective was to compare the baseline characteristics and developmental outcomes of infants who completed follow-up, infants who were LTF but seen by others in the community, and infants who were LTF but not seen by others (true LTF).Retrospective cohort study at a regional specialty center, including 262 patients referred to the NFU clinic who were born between 2014 and 2017, with a 24-month total follow-up period, such that assessment of all follow-up outcomes (NFU clinic attendance outcome, and clinician assessed developmental delay) was complete prior to March 2020. Multivariable logistic regression was used to model the odds of developmental delay, true LTF, and referral to developmental services at initial hospital discharge.Of 262 patients, 86 (33%) were LTF from the NFU clinic. Of these, 55 (64%) had developmental assessments by other providers. Of those LTFs from NFU but seen by other providers, the prevalence of clinician-assessed developmental delay at 24 months was 67%, compared with 45% of those who completed the NFU clinic (p < 0.001). Social risk factors (younger mothers, late or no prenatal care, maternal smoking, or referral for a social reason) were associated with higher odds of true LTF, but no different odds of referral to developmental services at hospital discharge.A majority of patients LTF from the NFU clinic had developmental assessments by others (64%). Social risk factors were associated with true LTF and missed developmental assessments.
Keywords: neonatal; high-risk infant; NICU; loss to follow-up